Reaction of Lead(II) with 2,6-Bis(1-hydroxy-2-naphthylazo) pyridine as a Spectrophotometric Determination of Phosphate and Citrate - Singh, Ishwar; K. Sharma, Ashok; K. Yadav, Sanjiv; Singh, Devender (Asian Journal of Chemistry, 2010)
A novel heterocyclic bis-azo dye, 2,6-bis(1-hydroxy-2-naphthylazo) pyridine (PBN) has been used as a chromogenic reagent for lead(II) to give a 1 : 2 (M : L) violet-coloured complex at pH 7.0- 8.5 absorbing maximum at 590 nm in a 50% aqueous ethanol medium. Sandell's sensitivity of the colour reaction is 0.0093 μg cm-2 with molar absorptivity of 2.22 x 104 L mol-1 cm-1. Job's method of continuous variations showed the composition to be Pb(II)-(PBN)2. Phosphate and citrate ions decompose the lead(II)- (PBN)2 complex quantitatively replacing PNB molecules from the complex. Using this ligand exchange reaction, the lead(II)- (PBN)2 complex has been used to determine 0.2-2.6 ppm of phosphate and 0.4-7.4 ppm of citrate spectrophotometrically.